How to make a rodent giant : genetic basis and genomic tradeoffs of gigantism in the capybara, the world's largest rodent (2017)
Differences in body size are arguably the most noticeable differences between species. However, how size is developmentally controlled to generate species-specific differences remain elusive. Moreover, theory predicts that inherent tradeoffs related to the evolution of big bodies, namely, a higher mutation load and an increased risk of cancer, should constraint the evolution of giants. We sequenced the genome of the capybara, the world's largest living rodent, to explore the genetic basis of gigantism in rodents and the genomic signatures of the gigantism-related tradeoffs. The evolution of big bodies amongst rodents appeared to correlate with a lower efficiency of purifying selection, consistent with a higher mutational load in the capybara relative to the rest of rodents. Moreover, several capybara genes involved in growth regulation by the insulin/insulin-like growth factor signaling (IIS) pathway were found to be under positive selection or accelerated evolution, and capybara-specific gene family expansions revealed a putative novel anticancer adaptation based on T-cell-mediated tumor suppression, consistent with cancer selection theory. Our analysis suggests that gigantism in the capybara likely involved four evolutionary steps: 1) Increase in body size by cell proliferation through the ISS pathway. 2) Coupled evolution of growth-regulatory and cancer-suppression mechanisms, possibly driven by intragenomic conflict. 3) The emergence of a cancer suppression mechanism and 4) a mutational load, possibly as an inevitable outcome of an increase in body size.